Review of the key results from the Swedish Obese Subjects (SOS) trial – a prospective controlled intervention study of bariatric surgery - Sjöström, L. (Journal of internal medicine, 2013)
Obesity is a risk factor for diabetes, cardiovascular disease events, cancer and overall mortality. Weight loss may protect against these conditions, but robust evidence for this has been lacking. The Swedish Obese Subjects (SOS) study is the first long‐term, prospective, controlled trial to provide information on the effects of bariatric surgery on the incidence of these objective endpoints. The SOS study involved 2010 obese subjects who underwent bariatric surgery [gastric bypass (13%), banding (19%) and vertical banded gastroplasty (68%)] and 2037 contemporaneously matched obese control subjects receiving usual care. The age of participants was 37–60 years and body mass index (BMI) was ≥34 kg m−2 in men and ≥38 kg m−2 in women. Here, we review the key SOS study results published between 2004 and 2012. Follow‐up periods varied from 10 to 20 years in different reports. The mean changes in body weight after 2, 10, 15 and 20 years were −23%, −17%, −16% and −18% in the surgery group and 0%, 1%, −1% and −1% in the control group respectively. Compared with usual care, bariatric surgery was associated with a long‐term reduction in overall mortality (primary endpoint) [adjusted hazard ratio (HR) = 0.71, 95% confidence interval (CI) 0.54–0.92; P = 0.01] and decreased incidences of diabetes (adjusted HR=0.17; P < 0.001), myocardial infarction (adjusted HR = 0.71; P = 0.02), stroke (adjusted HR=0.66; P = 0.008) and cancer (women: adjusted HR = 0.58; P = 0.0008; men: n.s.]. The diabetes remission rate was increased severalfold at 2 years [adjusted odds ratio (OR) = 8.42; P < 0.001] and 10 years (adjusted OR = 3.45; P < 0.001). Whereas high insulin and/or high glucose at baseline predicted favourable treatment effects, high baseline BMI did not, indicating that current selection criteria for bariatric surgery need to be revised.